The other lands of Israel : imaginations of the land in 2 Baruch - Lied, Liv Ingeborg (Supplements to the Journal for the study of Judaism, 2008)
Inspired by the perspective of Critical Spatial Theory, this book offers an interpretation of the conception of the Land of Israel in the early second century CE apocalypse 2 Baruch.